Indirect pump: unique presentation of a monochorionic–triamniotic triplet gestation complicated by TRAP sequence and successfully managed with radiofrequency ablation of the acardiac fetus. (24th June 2013) - Argoti, P. S.; Bebbington, M. W.; Johnson, A.; Moise, K. J.
ABSTRACT Twin reversed arterial perfusion (TRAP) sequence is a rare complication of multiple gestations. Only a few cases of TRAP sequence in monochorionic triplets have been reported. Here we report a case of TRAP sequence in a monochorionic–triamniotic triplet gestation treated with radiofrequency ablation of the acardiac fetus. The response to the radiofrequency ablation procedure and subsequent examination of the placenta support the hypothesis of an 'indirect' pump triplet. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.